2002
DOI: 10.1002/tea.10033
|View full text |Cite
|
Sign up to set email alerts
|

Promoting understanding of chemical bonding and spontaneity through student explanation and integration of ideas

Abstract: This article explores the effectiveness of intervention discussion sections for a college general chemistry course designed to apply research on student preconceptions, knowledge integration, and student explanation. Two interventions, on bond energy and spontaneity, were tested and intervention student performance was compared with that of a control group that did not use the experimental pedagogy. Results indicate that this instruction, which identifies students' initial conceptions and integrates those idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
119
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(127 citation statements)
references
References 29 publications
3
119
2
3
Order By: Relevance
“…Even after years of instruction it has been reported that about 50 % of students [8,9], including graduate students and postdoctoral scholars, continue to harbor inconsistent ideas about the energetics of bond breaking. Somehow traditional instruction has failed these students; even though they have surely been taught multiple times that bond breaking is endothermic, many have constructed erroneous ideas about this concept.…”
Section: Evidence-based Approaches To Teaching and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Even after years of instruction it has been reported that about 50 % of students [8,9], including graduate students and postdoctoral scholars, continue to harbor inconsistent ideas about the energetics of bond breaking. Somehow traditional instruction has failed these students; even though they have surely been taught multiple times that bond breaking is endothermic, many have constructed erroneous ideas about this concept.…”
Section: Evidence-based Approaches To Teaching and Learningmentioning
confidence: 99%
“…Socially mediated learning-whether as informal groups during lectures or more structured cooperative learning groups-has been shown to improve learning outcomes [9,12]. Providing students with opportunities to discuss the material allows them to organize and sort the information (especially when explaining to others), making retrieval and appropriate use more likely in the future.…”
Section: Evidence-based Approaches To Teaching and Learningmentioning
confidence: 99%
“…Similarly, knowledge gleaned from research on effective strategies for moving students from common misconceptions, or as some prefer to call them, "naive conceptions", to those accepted by mature scientists belong there (41)(42)(43)(44).…”
Section: Don't Neglect the Development Of Theorymentioning
confidence: 99%
“…Cross, Taasoobshirazi, Hendricks and Hickey (2008) identified that argumentation helps students to integrate their newly-acquired and existing knowledge, to learn concepts more thoroughly (Albe, 2008;Sadler, 2004), and to reduce misconceptions and become academically more successful. In addition, according to many experimental study results, students in argumentation group maintain better academic achievement than those in the traditional group (Ceylan, 2010;Deveci, 2009;Eryilmaz, 2002;Teichert & Stacy, 2002;Yeşiloğlu, 2007;Sağır and Kılıç, 2012;Kaya, 2005;Çelik, 2010;Özkara, 2011;Ceylan, 2010).…”
Section: Introductionmentioning
confidence: 99%